INTEGRATING ROUNDTABLE BRAINSTORMING INTO TEAM PAIR SOLO TECHNIQUE FOR IMPROVING STUDENTSâ PARTICIPATION IN WRITING OF DESCRIPTIVE TEXTS - Sutarno, author (JURNAL SMART, 2015)
The objectives of the study are to find out the application of integration of roundtable brainstorming into team pair solo technique in writing of descriptive texts and to investigate the improvement of studentsâ participation and achievement after taught by using the integration of the techniques. This study was an action research which was carried out through a preliminary study, first and second cycle activities. The subjects of this study were VII grade students of State Junior High School no.1 Semaka, Tanggamus, Lampung consisting of thirty two students. To collect the data, the researcher used instruments inform of interview, observation sheets, writing tests, and questionnaires. The findings of the research showed that studentsâ participation improved from the preliminary study, first and second cycle. In the preliminary study there were twenty six students classified as poor, six students classified as fair and no student classified as good in participation. While in the first cycle there were three students classified as fair and twenty nine students classified as good in participation and in the second cycle all students were classified as good in participation. The studentsâ writing also improved. The average score of students writing in the preliminary study was 53.31, first cycle was 64.41, and second cycle was 72.56.Key words: Roundtable Brainstorming, Team Pair Solo Technique, Studentsâ Participation, Writing Descriptive Texts